2015
DOI: 10.5812/asjsm.23811
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Relation Between Medial Tibial Stress Syndrome and Anatomic and Anthropometric Characteristics of Military Male Personnel

Abstract: Background:Medial Tibial Stress Syndrome (MTSS) is common among military recruits and to our knowledge; the factors that might put the military recruits at higher risk of incidence of MTSS are not well known.Objectives:This study was done to investigate the association between some anthropometric and anatomical factors and the prevalence of MTSS among military recruits.Patients and Methods:One hundred and eighty one randomly selected military recruits were included in this cross sectional study. Using history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…and White also found no significant differences for the BMI between the groups with and without MTSS (p = 0.917) in a sample of Australian navy recruits (52). Another two studies evidenced that the BMI is not associated significantly with the pathology reported in the military personnel (p >0.05) (54,55). One of the reasons for the differences found is that the systematic reviews with meta-analysis showed heterogeneity in the samples evaluated (athletes, civilian or military population).…”
Section: Discussionmentioning
confidence: 90%
“…and White also found no significant differences for the BMI between the groups with and without MTSS (p = 0.917) in a sample of Australian navy recruits (52). Another two studies evidenced that the BMI is not associated significantly with the pathology reported in the military personnel (p >0.05) (54,55). One of the reasons for the differences found is that the systematic reviews with meta-analysis showed heterogeneity in the samples evaluated (athletes, civilian or military population).…”
Section: Discussionmentioning
confidence: 90%
“…3 In military personnel, the incidence of MTSS was 7.2% to 35%. [5][6][7] For many military recruits, the nature and volume of the physical load on the lower legs increase as they adjust to basic training. 7 The lower extremity injuries military recruits sustain have negative effects on morbidity, training time, financial resources, and staffing.…”
Section: Commentarymentioning
confidence: 99%
“…[5][6][7] For many military recruits, the nature and volume of the physical load on the lower legs increase as they adjust to basic training. 7 The lower extremity injuries military recruits sustain have negative effects on morbidity, training time, financial resources, and staffing. 2,8,9 Based on research findings and practitioners' beliefs, experiences, biases, and paradigms, multiple risk factors are theorized for MTSS.…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations